The perception of resident physicians on the subject of mental health in the third year of the medical residency of a public university in Lima-Peru. - Miraval Rojas, Edgar (2020)
Introduction: Mental health is a topic that has taken on great importance in recent years and hasbecome a substantial part of many training programs around the world. Objective: Determine theperception of the resident doctor of the mental health subject during the last year of the medicalresidency. Methods: Observational, descriptive and transversal study with a sample of 130 students ofthe Mental Health course of the medical residency given by the Universidad Nacional Federico Villarrealwho were surveyed with a 10-question form that sought to know the students' perceptions about thiscourse. The sample was non-probabilistic. Results: Of the 130 students surveyed, 57.69% were womenand 13.85% were pediatricians, 57.69% were in a clinical specialty and 58.46% were in a residencyprogram. An exploratory analysis was made: concerning the importance of the course, differenceswith age range (p = 0.038) and residency modality (p = 0.005) were found. Besides, with respect to theacceptance of the course, differences with age range (p = 0.021) and type of residence (p = 0.053) werefound. Conclusion: The participants of the mental health course of the medical resident have goodacceptance of the subject and consider it important.